On the complexity of scoring acute respiratory distress syndrome: do not forget hemodynamics! - Repessé, Xavier; Aubry, Alix; Vieillard-Baron, Antoine (Journal of Thoracic Disease, 2016)
Acute respiratory distress syndrome (ARDS) remains associated with a poor outcome despite recent major therapeutic advances. Forecasting the outcome of patients suffering from such a syndrome is of a crucial interest and many scores have been proposed, all suffering from limits responsible for important discrepancies. Authors try to elaborate simple, routine and reliable scores but most of them do not consider hemodynamics yet acknowledged as a major determinant of outcome. This article aims at reminding the approach of scoring in ARDS and at deeply describing the most recently published one in order to highlight their main pitfall, which is to forget the hemodynamics.